SYARIAH CARD (TELAAH HUKUM AKAD/PERJANJIAN PERSPEKTIF ISLAM) - S. Purnamasari S. Purnamasari (At-Taradhi Jurnal Studi Ekonomi, 2012)
The validity of a contract in Islam has to be based on Al-Quran, Hadith and Ijtihad(legal thinking). One main principle in an Islamically sanctioned contract is that it is free fromusury, ambiguity and speculation. The rapid development of Islamic economy as shown by theestablishment of various Sharia financing units offering Sharia based products puts Islamic con-tracts (akad) in an important position. Foreseen disputes need to be anticipated so they will notcreate problems in the future. This necessitates a prudential standpoint and a compliance withIslamic law, so that the parties involved in an akad are legally protected. For this to happen, atransaction should be tied by a contract. The present article discusses how a Sharia credit card isanalysed from the perpective of Islamic contract.